Prediksi Kebangkrutan Altman Z-Score Modifikasi Komparasi Perusahaan Terbesar dan Terkecil Sub Sektor Tekstil dan Garmen di BEI - Widi Julianti; Muhammad Umar Mai; Ade Ali Nurdin (Indonesian Journal of Economics and Management, 2021)
This study aims to find out how the comparison of bankruptcy predictions at PT Argo Pantes Tbk & PT Sri Rejeki Isman Tbk for the 2015-2019 period, with the comparison indicator being total assets. The method used in this study is descriptive research with a quantitative approach and the data used are secondary data obtained from the financial statements published by PT Argo Pantes Tbk for the 2015-2019 period & the financial statements of PT Sri Rejeki Isman Tbk for the 2015-2019 period. The analytical technique used in this study is the Modified Altman Z-Score method that uses four ratio variables, namely Working Capital to Total Assets (X1), Retained Earnings to Total Assets (X2), EBIT to Total Assets (X3), and Book Value of Equity. to Book Value of Debt (X4). The results showed that during the 2015-2019 period (5 years) companies with small asset values (PT Argo Pantes Tbk) tended to have the potential to experience bankruptcy or were in distress compared to companies with large asset values (PT Sri Rejeki Isman Tbk). This condition is caused by the low financial ratios owned by PT Argo Pantes Tbk and the need for follow-up to deal with the problem so that the company avoids the risk of bankruptcy. Keywords: Bankruptcy Prediction Comparison, Altman Z-Score Modification